Low socioeconomic status is associated with adverse events in children and teens on insulin pumps under a universal access program: a population-based cohort study. Issue 1 (22nd June 2016) - Shulman, Rayzel; Stukel, Therese A; Miller, Fiona A; Newman, Alice; Daneman, Denis; Wasserman, Jonathan D; Guttmann, Astrid
Abstract : Objective: To describe adverse events in pediatric insulin pump users since universal funding in Ontario and to explore the role of socioeconomic status and 24-hour support. Research design and methods: Population-based cohort study of youth (<19 years) with type 1 diabetes (n=3193) under a universal access program in Ontario, Canada, from 2006 to 2013. We linked 2012 survey data from 33 pediatric diabetes centers to health administrative databases. The relationship between patient and center-level characteristics and time to first diabetic ketoacidosis (DKA) admission or death was tested using a Cox proportional hazards model and the rate of diabetes-related emergency department visits and hospitalizations with a Poisson model, both using generalized estimating equations. Results: The rate of DKA was 5.28/100 person-years and mortality 0.033/100 person-years. Compared with the least deprived quintile, the risk of DKA or death for those in the most deprived quintile was significantly higher (HR 1.58, 95% CI 1.05 to 2.38) as was the rate of diabetes-related acute care use (RR 1.60, 95% CI 1.27 to 2.00). 24-hour support was not associated with these outcomes. Higher glycated hemoglobin, prior DKA, older age, and higher nursing patient load were associated with a higher risk of DKA or death. Conclusions: The safety profile of pump therapy in the context of universal funding is similar to other jurisdictions and unrelated to 24-hour support. Several factors including higher deprivation were associated with an increased risk of adverse events and could be used to inform the design of interventions aimed at preventing poor outcomes in high-risk individuals.